1995
DOI: 10.5014/ajot.49.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Israeli Versus U.S. Preschool Children on the Miller Assessment for Preschoolers

Abstract: These findings indicate that the performance of Israeli children overall in these two age groups is not significantly different from the performance of U.S. children. If future research demonstrates that these findings are stable across all age groups and for larger samples, the implication is that the MAP can be administered and scored in Israel with the scoring methodology and normative information developed in the United States. However, because of the poorer performance of Israeli children on the Foundatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 2 publications
0
23
2
Order By: Relevance
“…Salvia and Ysseldyke (2004) described acculturation as an individuals' particular set of background experiences, opportunities to learn in informal and formal education settings and length of exposure to these. These differences in cultural suitability support the idea of acculturation and the view that certain skills and traditions are more appropriate in different cultures as a result of child-rearing practices and specific skill development (Katz et al, 2002;Schneider et al, 1995). Acculturation affects the assessment of intelligence and possibly cognition.…”
Section: Assessment Tasksmentioning
confidence: 76%
See 1 more Smart Citation
“…Salvia and Ysseldyke (2004) described acculturation as an individuals' particular set of background experiences, opportunities to learn in informal and formal education settings and length of exposure to these. These differences in cultural suitability support the idea of acculturation and the view that certain skills and traditions are more appropriate in different cultures as a result of child-rearing practices and specific skill development (Katz et al, 2002;Schneider et al, 1995). Acculturation affects the assessment of intelligence and possibly cognition.…”
Section: Assessment Tasksmentioning
confidence: 76%
“…To use an assessment cross-culturally, the instructions need to be translated with care and 'blind-back reviews' completed to demonstrate grammatical accuracy and comprehension (Schneider et al, 1995). The word choice may be explained by changes in the complexity of vocabulary through the translation process (Salvia & Ysseldyke, 2004).…”
Section: Languagementioning
confidence: 99%
“…These findings suggest that Japanese children are exposed to cultural traditions before they enter the educational system at about four years of age and that these traditions most likely influence fine motor performance skills because the Japanese spend much time in occupations such as brush painting, paper-folding and calligraphy writing. Schneider et al (1995) found differences between children in the United States and those in Israel on the Foundation Index of the MAP, which tests sensorimotor component skills. Possible reasons for these differences may be the emphasis on education and expectations from children, climate and temperature, physical space inside and outside the home, opportunities for gross motor activity and opportunities to explore through movement.…”
Section: Introductionmentioning
confidence: 96%
“…Child‐rearing practices can influence the amount and type of sensory information a child receives, and the type of skills taught and practised ( Cintas, 1988; Sturmey et al 1992 ; Victora et al , 1990 ). Cultural differences in child rearing have the potential to influence all areas of development ( Cintas, 1988; Schneider, Parush, Katz, & Miller, 1995; Werner, 1972). Although there are many similarities between the USA and Australia, there are also numerous racial, ethnic, social, political, economic, and historical differences.…”
Section: Introductionmentioning
confidence: 99%